2007
DOI: 10.1016/j.yexcr.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The EP4 receptor antagonist, L-161,982, blocks prostaglandin E2-induced signal transduction and cell proliferation in HCA-7 colon cancer cells

Abstract: Accumulating evidence indicates that elevated levels of prostaglandin E 2 (PGE 2 ) can increase intestinal epithelial cell proliferation, and thus play a role in colorectal tumorigenesis. PGE 2 exerts its effects through four G-protein coupled PGE receptor (EP) subtypes, named the EP1, EP2, EP3, and EP4. Increased phosphorylation of extracellular regulated kinases (ERK1/2) is required for PGE 2 to stimulate cell proliferation of human colon cancer cells. However, the EP receptor(s) that are involved in this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 42 publications
8
51
0
Order By: Relevance
“…PGE 2 stimulates cell proliferation in colorectal cancer cells via cAMP signaling (Loffler et al, 2008). EP4 involvement in proliferation of colorectal cancer cells was also demonstrated in several reports (Sheng et al, 2001;Mutoh et al, 2002;Cherukuri et al, 2007). Pozzi et al (2004) demonstrated that indomethacin, a nonspecific COX inhibitor, and COX-1 or -2 selective inhibitors prevented PGE 2 biosynthesis and proliferation of mouse colon adenocarcinoma cells.…”
Section: B Cancermentioning
confidence: 57%
See 2 more Smart Citations
“…PGE 2 stimulates cell proliferation in colorectal cancer cells via cAMP signaling (Loffler et al, 2008). EP4 involvement in proliferation of colorectal cancer cells was also demonstrated in several reports (Sheng et al, 2001;Mutoh et al, 2002;Cherukuri et al, 2007). Pozzi et al (2004) demonstrated that indomethacin, a nonspecific COX inhibitor, and COX-1 or -2 selective inhibitors prevented PGE 2 biosynthesis and proliferation of mouse colon adenocarcinoma cells.…”
Section: B Cancermentioning
confidence: 57%
“…PGE 2 increased expression of early growth response gene-1 (EGR-1), a downstream molecule of ERK, at the level of transcription. Cherukuri et al (2007) demonstrated that PGE 2 increased EGR-1 expression via CREB. They also showed that the EP4 receptor agonist PGE 1 -OH phosphorylated ERK in human colon adenocarcinoma cells, whereas the EP4 receptor antagonist L-161,982 blocked PGE 2 -induced ERK and CREB phosphorylation.…”
Section: B Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…PGE 2 or Butaprost Increased Erk1/2 Phosphorylation. Because phosphorylation of Akt and Erk1/2 has been suggested to mediate the growth-promoting effect of PGE 2 in other cancer cell types (Leng et al, 2003;Han and Wu, 2005;Krysan et al, 2005;Cherukuri et al, 2007), we examined the direct effects with PGE 2 on the phosphorylation of these proteins. As shown in Fig.…”
Section: Knockdown Of Ep2mentioning
confidence: 99%
“…L-748706, a selective COX-2 inhibitor, has also been found to reduce tumor multiplicity in carcinogen-induced esophageal tumor in rats by reducing PGE 2 levels (Stoner et al, 2005). In relation to the signaling mechanism, emerging evidence suggests that increased phosphorylation of extracellular signal-regulated kinases (Erk) 1/2 and protein kinase B (Akt) may be required for the stimulatory effect of PGE 2 on cell proliferation (Leng et al, 2003;Han and Wu, 2005;Krysan et al, 2005;Cherukuri et al, 2007).…”
mentioning
confidence: 99%